RESULTS FOR ANTIBIOTIC -LIKENESS ACTIVITY OF THE MUMIO AGAINST SALMONELLA SPP (Mongolian Journal of Agricultural Sciences, 2015)
In this study, antibiotic likeness activity of natural mineral-mumio (baragshun) against Salmonella spp. was studied. Purified mumio was diluted by 1:1, 1:5, 1:5, and absorbed into an antibiotic disk to test it on culture of Salmonella spp. which causes gastro-intestinal infection and food poisoning. Results of screening showed activity of mumio against Salmonella spp..The experiment was performed with a control group /antibiotic disk/ to compare the results.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 27-28